Developing Teaching Materials Based on Constructivism Arabic Learning in KTSP Curriculum/ تطوير المواد الدراسية على أساس المدخل البنائي لتعليم اللغة العربية في ضوء المنهج الدراسي على مستوى الوحدة التربوية - Ana Achoita (Al-Arabi: Jurnal Bahasa Arab dan Pengajarannya = Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2021)
The aim of this research is to improve teaching materials based on constructivist Arabic learning and oriented KTSP for first-class students of SMP  "Darul Quran" Singosari Malang. The problem statements of this research are: (1) how is the learning design (syllabus) of teaching materials based constructivism, (2) how is the design of teaching materials based on constructivism, and (3) how is the effectivity of teaching materials based on constructivism. The research method is development researchers in his research. Whereas the research object is first class students of SMP "Darul Quran" Singosari Malang, and all those students are the subject of this research as well. While Instruments used in research are interviews, observation, questionnaires, and tests.  Research results show that (1) learning design is very urgent in learning activities. Learning design is a reference to implement learning activities, (2) teaching materials based on constructivism is an effective way for Arabic learning in order to improve students ability in learning four language skills. So that the students can practice their knowledge in their daily lives, and (3) the average result of learning with these materials is "good". There are 3 students (12%) got "excellent", 7 students (28%) got "very good", 11 students (44%) god "good", and while 4 students (16%) got "fair".